(untitled) (LSP International Journal, 2020)
Encouraging students to speak during classroom activities is an effective strategy to improve their acquisition of the target language. Activities related to real life situation such as role play, debate and simulation provide substantial rehearsal and practice and they allow students to not just learn phrases, but also learn how to communicate in various circumstances. Recent studies have revealed that students who are exposed to learning using role play activities improve significantly in speaking competency. Hence, the aim of this study is to investigate how role play activities in an ESL classroom can be an innovative approach in improving students’ speaking skill. A total of nine undergraduate students from the Faculty of Computing in a public university in the Southern region of Malaysia were involved in this study. The main purpose for choosing the students as participants of the study was due to their low English proficiency based on their MUET results. The instruments used in this study were observation checklist and questionnaire. All the findings were tabulated and analysed qualitatively (observation checklist) as well as quantitatively (questionnaire). From the analysis carried out, it was evident that the students made positive improvement particularly in fluency, comprehension, context, and interactive communication. Besides that, the students felt that role play activities had brought positive effects on their English-speaking skills as obtained from the results of the questionnaire. Thus, it can be deduced that role play activities do have positive effects on students’ English-speaking skills.